(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2022)
In this study, researchers focused on How are the Meaning of Symbol of the Paduppa Dance in Bugis Customs in Sidrap Regency. The purpose of this study was "To find out How are the Meaning of Symbol of the Paduppa Dance in Bugis Customs in Sidrap Regency". To keep the focus of this research thoroughly and in-depth, this research uses qualitative research methods. The results of this study found that padduppa dance is a dance performed to welcome guests as a sign of respect for guests because it has a movement of sowing rice using bosara as a sign of respect.